Mekanisme Pertahanan Ego melalui Penyamaran Tokoh Utama dalam Anime 91 Days: Kajian Psikoanalisis Freud - I Kadek Arif Gunawan; Ni Luh Gede Meilantari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This research analyzes the phenomenon of identity concealment bu the main character in the anime 91 Days, Angelo Lagusa, who disguises himself as Avilio Bruno to revenge his family’s murder. The focus of this research is to identify and classify the ego defense mechanisms by Sigmund Freud employed by Angelo thoughout this process of concealment. Utilizing a descriptive qualitative method and a literary psychology approach, this research aims to provide a detailed description of how ego defense mechanism is manifested in the character’s actions and behavior. Data was collected through direct observation of all episodes in the series. The analysis reveals that four primary ego defense mechanisms are predominant. These four primary ego defense mechanisms are repression, sublimation, displacement and rationalization. Repression emerges as the most prominent mechanism, characterized by Angelo’s constant effort to suppress emotional drives (id), particularly in pain, rage and trauma into the subconscious to prevent them from interfering with his primary mission. Meanwhile, sublimation is evident when he channels his emotional energy into strategic and structured planning for his revenge. Displacement is observed in moments where his anger is redirected toward less threatening targets. Furthermore, rationalization is used by Angelo to justify his harsh and cruel actions with the logic of vengeance and justice. This research concludes that Angelo as Avilio in disguise is not merely a narrative strategy but an external representation of a complex internal psychological dynamic, where the ego functions as a mediator between the demands of the emotional id and the constraints of reality. Through this analysis, this research is expected to contribute to development of literary psychology studies, particularly in understanding the psychological construction of fictional characters through a Freudian theoretical lens.